2020
DOI: 10.1002/jdn.10003
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked adrenoleukodystrophy: Pathology, pathophysiology, diagnostic testing, newborn screening and therapies

Abstract: Adrenoleukodystrophy (ALD) is a rare X‐linked disease caused by a mutation of the peroxisomal ABCD1 gene. This review summarizes our current understanding of the pathogenic cell‐ and tissue‐specific roles of lipid species in the context of experimental therapeutic strategies and provides an overview of critical historical developments, therapeutic trials and the advent of newborn screening in the USA. In ALD, very long‐chain fatty acid (VLCFA) chain length‐dependent dysregulation of endoplasmic reticulum stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 182 publications
(262 reference statements)
2
128
0
6
Order By: Relevance
“…Interestingly, clinical presentation of adult-form X-ALD includes pain, bladder dysfunction, and impaired movement. 59 The association between MSMP and incontinence in the current study is consistent with this. LysoPC28:1 was found to be negatively associated with microvascular function improvement of hyperlipidemic patients undergoing lipoprotein apheresis, 51 which seemed to be attributed to lysoPC's ability of downregulating endothelial nitric oxide synthase, enhancing production of reactive oxygen species, inducing endothelial cell apoptosis, and inhibiting cell migration during damage repair.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, clinical presentation of adult-form X-ALD includes pain, bladder dysfunction, and impaired movement. 59 The association between MSMP and incontinence in the current study is consistent with this. LysoPC28:1 was found to be negatively associated with microvascular function improvement of hyperlipidemic patients undergoing lipoprotein apheresis, 51 which seemed to be attributed to lysoPC's ability of downregulating endothelial nitric oxide synthase, enhancing production of reactive oxygen species, inducing endothelial cell apoptosis, and inhibiting cell migration during damage repair.…”
Section: Discussionsupporting
confidence: 90%
“…LysoPC 26:0 is clinically used as the diagnostic marker for X-linked adrenoleukodystrophy (X-ALD), a condition caused by mutations in ATP-binding cassette subfamily D member 1 ( ABCD1 ) gene that encodes a peroxisomal transmembrane protein, resulting in accumulation of very-long-chain fatty acids, particularly C26:0, and subsequent PC 26:0 and lysoPC 26:0 before the onset of demyelination. 13 , 57 , 59 Gong et al 20 reported that in cultured ABCD1-deficient microglia, lysoPC 26:0 enhanced the expression of phagocytosis-related marker milk fat globule-EGF factor 8 (MFGE8), aggravated phagocytosis, and led to neuronal injury. Interestingly, clinical presentation of adult-form X-ALD includes pain, bladder dysfunction, and impaired movement.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenoleukodystrophy (ALD) is a very important cause of PAI because of associated progressive neurological features ( 90 ). The X-linked form of ALD due to defects in ABCD1 usually presents in childhood, and sometimes with adrenal-only features.…”
Section: Primary Adrenal Insufficiencymentioning
confidence: 99%
“…31 Similarly, the ABC transport adrenoleukodystrophy protein ( ABCD1 ) is present in peroxisomal membranes and works to transport fatty acids into peroxisomes for degradation. Mutations in ALDP are associated with X-linked adrenoleukodystrophy, 32,33 a condition brought to the attention of many through the Hollywood movie “Lorenzo’s Oil.” Cystic fibrosis transmembrane conductance regulator is a 1480 amino acid integral membrane protein that normally resides in the apical membrane of polarized epithelial cells lining the airways, GI tract, vas deferens, pancreatic duct, biliary tree, and sweat gland ducts. 5,34 -38 Like all members of the ABC family, CFTR is composed of 2 membrane-spanning domains (TMD-1 and -2), which anchor the protein in the plasma membrane, and 2 nucleotide-binding domains (NBD-1 and -2), which form a heterodimer to bind and hydrolyze ATP, presumably to control channel gating (CFTR opening and closing).…”
Section: Symptom-based Therapiesmentioning
confidence: 99%
“…31 Similarly, the ABC transport adrenoleukodystrophy protein (ABCD1) is present in peroxisomal membranes and works to transport fatty acids into peroxisomes for degradation. Mutations in ALDP are associated with X-linked adrenoleukodystrophy, 32,33 a condition brought to the attention of many through the Hollywood movie "Lorenzo's Oil." Cystic fibrosis transmembrane conductance regulator is a 1480 amino acid integral membrane protein that normally resides in the apical membrane of polarized epithelial cells lining the airways, GI tract, vas deferens, pancreatic duct, biliary tree, and sweat gland ducts.…”
Section: Precision Medicinementioning
confidence: 99%